(Pseudo)Philosophical (Pseudo)Expertise - Paszkowski, Piotr (Roczniki Filozoficzne, 2025)
Although the term “pseudophilosophy” is rarely used in subject literature, the accusation behind it – namely, the accusation of “not being a true philosopher” – is a phenomenon worth attention. In this article, I analyze three contemporary concepts of pseudophilosophy (Rescher, Merrill, and Moberger). I note that they share a common structure, and thus face similar problems, which I describe later (the problem of “bad philosophy” and the issue of uninformative criteria). I then present my own proposal for overcoming the impasse in the discussion of pseudophilosophy – namely, a shift away from classic investigations into the essence of philosophy and a focus instead on the expectations regarding the social role of a philosopher. I argue that framing the issue of pseudophilosophy in terms of (pseudo)expertise enables such explication of assumptions underlying the accusation of pseudophilosophy, which remained hidden within previous approaches.